Homonimika rosyjska jako przedmiot zainteresowania polskich leksykologów i leksykografów. Na marginesie najnowszych prac Jerzego Kaliszana - Wojan, Katarzyna (Studia Rossica Posnaniensia, 2018)
The text is dedicated to Professor Jerzy Kaliszan, an outstanding Polish researcher of homonymy in the Russian language, the author of significant monographs and the first Polish dictionary of Russian homographs. The article is a review of Polish academic literature on Russian homonymy including both intra- and interlinguistic aspects (relations between Polish and Russian). In the first part, the author outlines the most important theoretical and lexicographical studies of Polish scholars. The second part is devoted to a description of Jerzy Kaliszan’s achievements in the field of lexical and word-formation homonymy, including lexemes’ homography.